Deformation Behaviour of Mg-Based Matrix Composites - Lukac, Pavel; Trojanova, Zuzanka (Communications - Scientific letters of the University of Zilina, 2009)
The influence of various reinforcements on mechanical properties and deformation behaviour of some magnesium alloys was studied. Strength and deformation behaviour were investigated over a wide temperature range. The reinforcement was in the form of short fibres or particles. The volume fraction of the reinforcement significantly influences the properties of a composite. The interface between the matrix and the reinforcement has a great deal of importance in determining the properties of the composite. Thermal stresses generated at the interface play a very important role.